Operating lists are created by rational algorithms and use of power. What can a social scientific view offer surgeons? - Engelmann, Carsten; Grote, Gudela; Geyer, Siegfried; Ametowobla, Dzifa (Langenbeck's archives of surgery, 2017)
Purpose Algorithms for surgical operation planning are evidence-based. However, choices sometimes have to be made between medically equal solutions e.g. for staffing of sought-after operations. Such decisions are heavily influenced by micropolitics and power. The article examines the array of highly manipulated processes around operation theatre allocation of convenient time slots or staff, which play out in various ways in all of the world’s main regional surgical cultures. Method Essay supported by empiric data from an ethnographic power-analysis targeted to senior executive surgeons. Operations were categorized into “Interesting” (i.e. career-promoting) and “Uninteresting” (i.e. routine) operations. Results Fifty nine executives responded. Only one respondent contested the categorization of operations into Interesting and Uninteresting. The two categories were staffed according to significantly different criteria ( p < 0.05). These were classified as Rational (e.g. “surgical expertise”), Social (e.g. “equity”), and Political (e.g. “status”). For Interesting operations, Rational criteria were deemed most relevant, while for the Uninteresting operations “equity” was ranked top. Moreover, we found significant differences between surgeons’ and external observers’ (experienced clerical and nursing staff) assessments of staffing decisions, the latter ranking Political motives higher. Decisions were almost exclusively negotiated among surgeons. 33% of respondents said they used subterfuges such as withholding information, incorrect duration-statements, and barter arrangements to defuse possible conflicts. Conclusions Operating Lists are not merely the product of rational resource optimization. This article demonstrates the methodic feasibility of academic investigation into the typically tacit micro-political mechanisms in List-making. Developing such research further may potentially concern the practice and outcome of surgery.